MEMBANGUN SISTEM MANAJEMEN PERGUDANGAN MENGGUNAKAN ARSITEKTUR THREE-TIER - ., Anggreawan; Hamzah, Amir; Iswahyudi, Catur (Jurnal Jarkom, 2015)
ABSTRACT Three-tier architecture is an innovation of client server architecture. In the three-tier architecture, there are services presentation or user interface logic is placed on the client machine. Issued on the business logic and the client code is placed in the middle level. Data services layer contains the database server. Each level in the three-tier models are on a separate computer. Three-tier model concept is a concept that divides functionality into layers, applications gain scalability, and security. Currently the system at PT. Ungaran Sari Garment has been computerized in handling the transaction flow of goods in and out. However, the application still has the disadvantage that the application can only be used by a single computer (stand alone) and standard office without any database and system well. With the advantages of three-tier architecture, then build warehouse management system using three-tier architecture to assist in arranging entry and exit of goods to the warehouse, making the system more efficient in terms of use. Results from this study is the implementation of the warehousing system with three-tier architecture using SQLyog as its database can be used to input data entry and exit of goods to the warehouse, checking periodically warehousing reports in accordance with the functionality of each admin. By using a three-tier architecture as not to burden-sharing functionality on the server side and the client, because can use any computer that has been given permission by the server and are interconnected by a network. On the client side is only installation any web browser Keywords : Warehouse management system, Website, Client server, Three-tier.